THE ENHANCEMENT OF PROBLEM SOLVING SKILL BY INSTRUCTIONAL MODEL BASED ON SERVICE LEARNING WITH PROBLEM BASED LEARNING FOR STUDENTS IN AN ENVIRONMENTAL IMPACTED AREA - Buddee , Suriya; Kongson, Rungtiwa (Journal of MCU Nakhondhat, 2023)
The objective of the research was to enhancement of problem solving skill by instructional model based on service learning with problem based learning for students in an environmental impacted area. The sample population was the class of 26 students of grade 12 in the Science and Maths program of Wiangkaen Wittayakhom School of the Secondary Educational Service Area Office Chiangrai the 1st semester of the education year 2022, using the Cluster Random Sampling Method. Various tools were employed to do the research which included 1) Instructional model based on service learning with problem based learning to enhance problem solving skill for students in an environmental impacted area. 2) Problem solving skill evaluation form. Other tools included data analysis, arithmetic mean, standard deviation, percentage and independent t-test. The research findings indicates that all participating students had higher problem solving skills after the class conducted using the Instructional model based on service learning with problem based learning to enhance problem solving skill when compared prior to the research, at a statistical significance of .01. furthermore, it was found that problem solving skills during studying with the Instructional model based on service learning with problem based learning to enhance problem solving skill for students in an environmental impacted area, in overall, was very high at an average of 4.27 which was 85.40 percent. As for students’ behaviour and characteristics, the researcher found that the students showed the highest level compared to other categories at 4.66 or 93.20 percent. Other characteristics which include problem analysis, strategic planning to solve problems, applications of problem solving skills to solve real world context, ability to identify related problems and the ability to summarize the result of problem solving were all at high levels at 85.80 percent, 84.80 percent, 83.40 percent, 83.00 percent and 82.20 percent respectively.